Description of Personal Hygiene in Post-Major Surgery Patients - Kurniati, Nia; Deli, Hellena; Utami, Sri (CV. Rayyan Dwi Bharata, 2024)
Major surgery is a surgical procedure that has a high risk for the patient and is usually extensive surgery and uses general anesthesia. One way to prevent major surgical wound infections is personal hygiene. The aim of this research is to determine the description of personal hygiene in patients after major surgery. Method: This research uses a quantitative approach with a descriptive research design. The research sample was 115 post-major surgery patients with the sampling technique used was purposive sampling. Results: a total of 115 respondents found that personal hygiene for patients after major surgery in general was minimal care for 83 people (72.2%). It is hoped that the hospital will maintain and improve the patient's personal hygiene independence so that complications do not occur.